Risk-based approach for food safety applied to pork value chain in Vietnam - Hung Nguyen-Viet; Sinh Dang Xuan; Tran Thi Tuyet Hanh; Phuc Pham Duc; Grace, Delia; Unger, Fred; Makita, K. (International Livestock Research Institute, 2015)
Food-borne disease is a major public health issue in Vietnam. The contamination of popular foods can occur all along the food value chain. It is important to understand how and where food safety issues arise to mitigate and prevent food-borne diseases. Risk-based approach is a tool for managing food safety, however in Vietnam it is rarely applied and the capacity for application is still lacking however risk-based approach it is rarely applied and the capacity for application is still lacking. This paper describes the risk assessment training and research for pork along pig value chain in Vietnam. Risk assessment short courses and training curriculum were developed and taught at universities to strengthen the risk assessment capacity of partners. In parallel and after the training, risk assessment case studies were conducted to assess health risks related to pork consumption in the context of a pig smallholder value chain and pork traded in informal markets. Microbial (Salmonella) in 1275 pork and environmental samples collected at farm, slaughterhouse, and market and consumption level were analyzed. Pork consumption behavior and cross-contamination modalities during pork preparation were assessed. Chemical hazards (antibiotic and heavy metal residues) in 190 pork samples from markets were also analyzed. Results showed that Salmonella contamination in carcass swab in slaughterhouse was 39%, and in the final pork at market 45% with an average concentration of 9 MPN/g was recorded. 50% and 16.7% pooled samples were positive with sulfamethazine and chloramphenicol, with an average residue level of 156 µg/kg and 0.54 µg/kg respectively. A quantitative risk modeling is being developed and integrates information on contamination along the pork value chain to characterize the health risk caused by Salmonella. Results of risk modeling will be presented and risk mitigation options discussed.